Chapter El teatro del Siglo de Oro en el fondo Orsi de la Biblioteca Estense de Módena - Vuelta García, Salomé (Studi e saggi, 2020)
This paper offers an overall study of the texts derived from the Spanish classical theater contained in the Orsi collection of the Estense Library of Modena, which has so far not been adequately investigated. The remarkable interest of Giovan Gioseffo Orsi (1652-1733) and his entourage for the Spanish theater emerged, played in the public theaters, private villas, academies and Jesuit colleges of Modena and Bologna between the end of the XVII and the beginning of the XVIII century. In addition, several unknown adaptations and remakes come to light, deriving from Spanish pièces included in the Diferentes autores collection - which had a considerable European circulation -, and some canovacci, long considered lost, dating back to the companies of the professional comedians Giovanni Andrea Cavazzoni and Luigi Riccoboni. The analysis conducted on some of these texts, of which there are multiple versions, allows us to go into the translator's laboratory, greatly increasing our knowledge of the theatrical rewriting methods of the time.